Higher Education General Information Survey (HEGIS), 1982: Fall Enrollment ([Verlag nicht ermittelbar], 1985)
The Higher Education General Information Survey (HEGIS) series was designed to provide comprehensive information on various aspects of postsecondary education in the United States and its territories (American Samoa, Guam, Puerto Rico, the Virgin Islands, and the Marshall Islands) and Department of Defense schools outside the United States. Data are available for both public and private two-year and four-year institutions. The HEGIS Fall Enrollment component for 1982 sought enrollment data from 3,327 institutions of higher education. Key data elements, presented for up to 12 record types for each institution (corresponding to major fields of study and total enrollments summary), include number of full-time and part-time students by class level, sex, race, and total number of students. Additional data include the institutions' type of accreditation and type of calendar system.